High‐melt‐elasticity poly(ethylene terephthalate) produced by reactive extrusion with a multi‐functional epoxide for foaming. Issue 8 (26th October 2017) - Yang, Zhaoping; Xin, Chunling; Mughal, Waqas; Li, Xiaogang; He, Yadong
ABSTRACT: A multi‐functional epoxide oligomer, Joncryl ADR‐4368 (ADR), is used as a modifier to prepare foamable poly(ethylene terephthalate) (PET) by reactive extrusion and compared with common tetra‐functional modifier pyromellitic anhydride (PMDA) as a reference. Torque evolution reveals that ADR has a faster reaction with PET than PMDA. The reactions generate long‐chain branches and gel structures, which are confirmed by rheological methods. Shear rheological studies show that PET modified with both ADR and PMDA display higher complex viscosity and lower loss tangent than unmodified sample. In particular, at a given viscosity level, ADR leads to a lower loss tangent than PMDA. Moreover, compared to PMDA, the addition of ADR results in a higher die pressure during extrusion and a more pronounced strain hardening during uniaxial elongation. These results indicate that ADR‐modified PET is less viscous but more elastic than PMDA‐modified PET. Owing to the higher elastic properties, ADR‐modified PET presents better foaming performance in batch foaming process with CO2 as a blowing agent. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45805. Abstract :